DETEKSI DAN IDENTIFIKASI KAPANG PADA PROSES BIODETERIORASI BATUAN CANDI PAWON - Putri Nur Indahsari; Bernadetta Octavia; Nahar Cahyandaru (Balai Konservasi Borobudur Magelang, 2022)
This research attempts to know diversity of the moulds found in the biodeterioration process of Pawon Temple stone and identifying the type of damage caused by the moulds in the biodeterioration process of Pawon Temple stone. Survey sampling of Pawon Temple rocks based on the conditions: damp, weathered, cracked, and there is a yellowish-white crust. Sampling is done by swab technique using sterile cotton bud and scraping technique using scalpel. Identification of macroscopic and microscopic mold with profile matching method based on the book Pengenalan Kapang Tropik Umum, Descriptions of Medical Fungi, Identification of Pathogenic Fungi. The identification finds six genus are Penicillium (13%), Paecilomyces (59.4%), Mucor (15.9%), Stachybotrys (2.8%), Aspergillus (4.3%) and Cladosporium (2.8%). The genus of kalag in Pawon Temple is based on the search of libraries and journals potentially as agents of color formation, exfoliation of rocks and formation of postules and alevol.